The Effect of Dragon Fruit Extract Concentration and Fermentation Duration on the Funtional Properties of Nata from Palm Sap - Nur Fadhilah Babyonggo; Sunarto Kadir; Yoyanda Bait; Vivien Novarina Kasim (GLOBAL HEALTH SCIENCE GROUP, 2026)
Changes in modern consumption patterns show a tendency toward low daily dietary fiber intake. One potential solution to increase fiber intake while utilizing agricultural waste is through the use of red dragon fruit peel (Hylocereus polyrhizus). The objective was to analyze the effect of dragon fruit peel extract concentration and fermentation duration on the functional properties of nat a from palm sap. The study used a complete randomized design (CRD) with multiple factors. Factor x was the concentration of dragon fruit peel extract at 10%, 20%, 30%, and 40%, and factor y was the fermentation duration at 7 days, 14 days, and 21 days, with each treatment repeated three times. Data analysis was performed using Analysis of Variance (ANOVA). Significant differences between treatments were analyzed using DMRT. The results showed that the treatment with 40% dragon fruit peel extract concentration and a fermentation period of 14 days showed an increase in antioxidant response and good nutritional content with an antioxidant response of 110.5 ppm (moderate). There is an effect of concentration and fermentation duration on antioxidant response, fiber, thickness, pH, mold/yeast, and ALT, as indicated by a ρ value of 0.000 < α 0.05.